Digital loyalty card 'big data' and small business marketing: Formal versus informal or complementary?. (June 2015) - Donnelly, Christina; Simmons, Geoff; Armstrong, Gillian; Fearne, Andrew
This article proposes that a complementary relationship exists between the formalised nature of digital loyalty card data, and the informal nature of small business market orientation. A longitudinal, case-based research approach analysed this relationship in small firms given access to Tesco Clubcard data. The findings reveal a new-found structure and precision in small firm marketing planning from data exposure; this complemented rather than conflicted with an intuitive feel for markets. In addition, small firm owners were encouraged to include employees in marketing planning.